Insensitivity of Bacteria to Proposed Antimetabolites of d-Alanyl-d-Alanine - Gale, Glen R. (1973)
α-Aminoisobutyryl-d-alanine, d-alanyl-α-aminoisobutyric acid, and α-amino-isobutyryl-α-aminoisobutyric acid, proposed as antimetabolites of d-alanyl-d-alanine in bacterial cell wall synthesis, failed to inhibit bacterial growth.